HGV2011: Personalized Genomic Medicine Meets the Incidentalome - Sayres, Melissa A. Wilson (2012)
The 12th International Meeting on Human Genome Variation and Complex Genome Analysis (HGV2011: Berkeley, California, USA, 8th–10th September 2011) was a stimulating workshop where researchers from academia and industry explored the latest progress, challenges, and opportunities in genome variation research. Key themes included progress beyond GWAS, variation in human populations, use of sequence data in medical settings, large-scale sequencing data analysis, and bioinformatics approaches to large datasets.